Development of Electronic Commerce on Tourist Traveling - W Novianti; R D Pratama (International Journal of Research and Applied Technology (INJURATECH), 2021)
The research aims to specify the effect of the expansion of e-commerce on the ticket booking business. The method used in this research was descriptive analysis, which was a method that presents a complete picture of the phenomena that occur in the case raised. Besides that, this study identifies the extent of the impact resulting from the development of e-commerce on the ticket booking business, as well as the benefits to be gained from the results of the ticket booking. The results of this study prove that booking tickets online is very efficient and makes it easy in the transaction process. Based on the analysis conducted, the impact of the development of e-commerce on the online ticket booking business has a major effect on the development of e-commerce. The research concluded that the effect of e-commerce development has a big influence on people's interest in booking tickets online.